Assessment of water pollution of the South Morava River (Serbia) by statistical and index methods - Aleksandar Zdravković; Goran Petković; Nikolić Dragana Marković; Danijela Stojadinović; Ivanka Ristić; Nebojša Ristić; Tanja Nikolić (Zaštita Materijala)
Factor analysis/principal component analysis (FA/PCA), applied to 16 physico-chemical parameters at three different monitoring sites (Mojsinje, Korvingrad, and Ristovac) of the South Morava River in 2015, and from 2011-2018 for station Ristovac, extracted two and four varimax factors which explain 100.000 and 90.874 % of the total variance in water quality, respectively. The relationships among the stations and years obtained by cluster analysis (CA) categorize observed objects in different quality levels. Parameters responsible for pollution of the South Morava River are related to point (industrial/sewage effluents), non-point (runoff from arable land and erosion), and natural source (a mineral component of the river water). The results of the water pollution index (WPI) method for 2015 have shown that the South Morava River at Korvingrad station represents a "moderately polluted" water body (class III), but at Mojsinje and Ristovac station a "polluted" water body (class IV). The obtained ecological potential values indicated that water quality at the Korvingrad station corresponds to class II, "good ecological potential". The surface water at Mojsinje and Ristovac stations deviated from the required ecological water standards by the European Union Water Framework Directive (EU WFD), class III. The South Morava River had the highest load of nutrients (PO4-P and TP) and organic matter (TOC) at Ristovac station, which was confirmed by the index and comparative method (polluted water with poor ecological potential) in period from 2011-2018. A comprehensive analysis of the paper identified a decreasing trend in pollution of the South Morava River, primarily at Ristovac station.